Reputation Strategy for Special Schools (SLB) Sambit District Student Home - Khotimah, Rohma Khusnul; Lestarini, Niken; Purwati, Eli; Megantari, Krisna (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2024)
Education in a country has a very important role in ensuring the survival of the nation, because education is a vehicle for increasing and developing one's potential so that quality human resources can be achieved. Reputation is an important asset for an organization because public trust is built on reputation. Reputation is not something that is fixed. Sometimes the reputation increases and sometimes decreases. For this reason, efforts are needed to maintain reputation. The approach used in this study is a qualitative descriptive approach, in which the researcher directly obtains information from informants while still referring to qualitative research guidelines. The determination of informants was carried out using a purposive sampling technique. Using internal reputation strategies (internal school) and external actions (external schools) can be used as a basis for determining strategies to build school reputation so that later it can optimize the implementation process and also develop strategies to build school reputation.